Problemy reformy systemu podatkowego - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1987)
The article discusses the indispensability of the reform of Polish tax system. The author begins with the economic, social and political conditions of such a reform. The above background serves him for presenting the shortcomings of the present tax system. The need of tax reform with respect to socialized economy, non-socialized economy and the population has been stressed. As far as the taxes levied on socialized economy are concerned, the author postulates to replace the turnover tax with the value added tax, what would result in limiting fiscal stringency of the former. As to the income tax, the author suggests to reduce its fiscal effects. They limit the self-financing capabilities of enterprises, especially their investment capacities. With respect to taxes levied on non-socialized economy, the postulate of simplifying the forms of their assessment and collection has been put forth. The present forms are not always understandable for taxpayers and, in consequence, difficult to apply. Besides, in this way they limit the scope of private economic activity. The author formulates also the argument about the need of preparing the conception of universal income tax levied on the population. In that context he suggests taking into account the methods of shaping the level of income and prices. He ends his consideration with the thesis pointing to the urgent necessity of reforming the tax system.
The problem of the Tax System Reform